Perlindungan Hukum Bagi Pengguna Game Online Dirugikan Karena Tutupnya Sistem Elektronik Game Online Di Indonesia Secara Sepihak - Nugroho, Muhammad Kelvin Adi; Nasution, Krisnadi (CV. Era Digital Nusantara, 2025)
With the growing popularity of online games in Indonesia, numerous players purchase virtual items within these games. This study focuses on two primary objectives. First, it seeks to analyze the legal protection available to online game players in Indonesia against the unilateral shutdown of game servers by Electronic System Providers, as regulated under Article 1694 of the Civil Code. If an online game server is closed unilaterally, virtual items owned by players, considered akin to goods, may be affected. Second, the study aims to explore solutions for addressing losses incurred by players due to such server closures. Utilizing a normative juridical approach with an emphasis on Article 1694 of the Civil Code, the research relies primarily on library-based data collection techniques. The findings indicate that online game players, as rightful owners of virtual items, are entitled to the full restitution of their items. Virtual items, though non-physical, are treated similarly to tangible goods. In cases where these items are deleted or lost due to server shutdowns, Electronic System Providers bear responsibility for returning the affected players’ virtual goods. Dispute resolution can be pursued through litigation or non-litigation methods, including consultation, conciliation, mediation, and negotiation.